2019
DOI: 10.1016/j.ebiom.2019.11.006
|View full text |Cite
|
Sign up to set email alerts
|

Two years of treatment with the recombinant grass pollen allergy vaccine BM32 induces a continuously increasing allergen-specific IgG4 response

Abstract: Background: BM32, a grass pollen allergy vaccine containing four recombinant fusion proteins consisting of hepatitis B-derived PreS and hypoallergenic peptides from the major timothy grass pollen allergens adsorbed on aluminium hydroxide has been shown to be safe and to improve clinical symptoms of grass pollen allergy upon allergen-specific immunotherapy (AIT). We have investigated the immune responses in patients from a two years double-blind, placebo-controlled AIT field trial with BM32. Methods: Blood samp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
38
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 32 publications
(41 citation statements)
references
References 50 publications
1
38
0
Order By: Relevance
“…Of note, at visit 8, 4 weeks after the fifth injection, the preS-specific cumulative IgG 1 and IgG 4 responses reached up to 1.8 mg/ml with median preS-specific IgG 1 and IgG 4 level of 106.8 μg/ml and 30 μg/ml, respectively and thus should eventually be able to neutralize HBV even when soluble preS antigen is present in the blood of chronic HBV patients. While preS-specific IgG 1 declined quickly, preS-specific IgG 4 was maintained and from allergen-specific immunotherapy studies conducted with BM32 we know that IgG 1 titers can be restored and IgG 4 continues to grow after only one booster injection [14] . Our current study provides thus support for the latter speculation and encourages performing clinical trials with BM32 to investigate if it can be indeed used for therapeutic vaccination.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Of note, at visit 8, 4 weeks after the fifth injection, the preS-specific cumulative IgG 1 and IgG 4 responses reached up to 1.8 mg/ml with median preS-specific IgG 1 and IgG 4 level of 106.8 μg/ml and 30 μg/ml, respectively and thus should eventually be able to neutralize HBV even when soluble preS antigen is present in the blood of chronic HBV patients. While preS-specific IgG 1 declined quickly, preS-specific IgG 4 was maintained and from allergen-specific immunotherapy studies conducted with BM32 we know that IgG 1 titers can be restored and IgG 4 continues to grow after only one booster injection [14] . Our current study provides thus support for the latter speculation and encourages performing clinical trials with BM32 to investigate if it can be indeed used for therapeutic vaccination.…”
Section: Discussionmentioning
confidence: 97%
“…Therapeutic vaccination with BM32 would therefore have the advantage that one can build up a quite long-lasting concentration of antibodies which are approximately equimolar as compared to an infusion of 20 mg myrcludex B. In this context it should be mentioned that only one single booster injection of BM32 was sufficient to boost specific antibody levels [14] . Therapeutic vaccination would thus have considerable advantages over small molecular inhibitors because only few injections with booster injections in long intervals (i.e., several months) would maintain protective antibody levels and the costs for treatment would be also low.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Three more important observations were made in the clinical trials with BM32: First, BM32 induced allergen-specific IgG and in particular a continuously growing allergen-specific IgG 4 response without boosting allergen-specific IgE as it is observed for all other AIT vaccines ( 80 ). Second, BM32 did not boost T cell and inflammatory cytokine responses specific for grass pollen allergens and thus seems to have no priming effect on allergen-specific T cell responses ( 80 ). Third, it was found that BM32 induced also IgG antibodies against HBV, which blocked the infection of in vitro cultured liver cells and thus it seems that BM32 also protects against HBV infection ( 81 ).…”
Section: Introductionmentioning
confidence: 99%
“…Usually, after 3 years of AIT treatment beneficial effects continue for a few years, even when AIT has been discontinued 20 . These long‐term effects may be attributed to the persistence of high‐affinity and functional allergen‐specific IgG 4 antibodies 21‐23 . However, boosting of antibody responses may become necessary after discontinuation.…”
Section: Introductionmentioning
confidence: 99%